2012
DOI: 10.1098/rsbl.2011.1111
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of burrow casting as a research tool in deep-sea ecology

Abstract: Although the deep sea is the largest ecosystem on Earth, its infaunal ecology remains poorly understood because of the logistical challenges. Here we report the morphology of relatively large burrows obtained by in situ burrow casting at a hydrocarbon-seep site and a non-seep site at water depths of 1173 and 1455 m, respectively. Deep and complex burrows are abundant at both sites, indicating that the burrows introduce oxygen-rich sea water into the deep reducing substrate, thereby influencing benthic metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Callianassid shrimps plaster their burrow walls with mucus, resulting in the stabilization of burrows for extended periods of time (Dworschak, 1998). Interestingly, it has been suggested that the burrows of callianassid decapods act as preferred fluid expulsion pathways in the shallow subsurface at seeps (Peckmann et al, 2007;Seike et al, 2012;Wetzel, 2013;Wiese et al, this volume). The recent finding of putative callianassid burrows within reducing sediments surrounding 13 C-depleted carbonates from pockmarks in the Mediterranean Sea (Taviani et al, 2013) provides additional support for the role of bioturbation in the establishment of the plumbing system in the shallow subsurface at seeps.…”
Section: Genesis Of Pipesmentioning
confidence: 99%
“…Callianassid shrimps plaster their burrow walls with mucus, resulting in the stabilization of burrows for extended periods of time (Dworschak, 1998). Interestingly, it has been suggested that the burrows of callianassid decapods act as preferred fluid expulsion pathways in the shallow subsurface at seeps (Peckmann et al, 2007;Seike et al, 2012;Wetzel, 2013;Wiese et al, this volume). The recent finding of putative callianassid burrows within reducing sediments surrounding 13 C-depleted carbonates from pockmarks in the Mediterranean Sea (Taviani et al, 2013) provides additional support for the role of bioturbation in the establishment of the plumbing system in the shallow subsurface at seeps.…”
Section: Genesis Of Pipesmentioning
confidence: 99%
“…assemblages associated with hydrothermal vents and methane seeps in the Okinawa Trough and Sagami Bay could be explained by temperature and salinity . Although the vertical distribution of infauna is still unclear, the importance of infauna as a disturber of sediment has been noted in deepsea reducing environments (Seike et al 2012).…”
Section: Faunal Zonation In a Vent Fieldmentioning
confidence: 99%
“…The burrowing activity of seep organisms can further enhance the fluid circulation by creating conduits (e.g. Seike et al, 2012) which enhance the fluid release on one hand (e.g. Wiese et al, 2015), but also fluid reflux on the other.…”
Section: Paleocene Hydrocarbon-seep Carbonates From the Basilika Formmentioning
confidence: 99%